2017
DOI: 10.5489/cuaj.4170
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smartphone digital photography, email, and media communication on emergency room visits post-hypospadias repair

Abstract: Introduction: Advances in communication technology are shaping our medical practice. To date, there is no clear evidence that this mode of communication will have any effect on unnecessary postoperative emergency room (ER) visits. We aim to evaluate the effect of email and media communication with application of smartphone digital photography on post-hypospadias repair ER visit rates. Methods: This prospective cohort study included all patients who underwent hypospadias repair performed by a single surgeon fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In other surgical specialties, the use of a nurse answering service or even smart phones for wound evaluation has been shown to decrease presentation to the emergency department for nonacute issues. 14,15 Physicians on-call could have reassured Skin and soft tissue (10) 5 (50%) 0 (0%) 0 (0%) 10 (100%)…”
Section: Discussionmentioning
confidence: 99%
“…In other surgical specialties, the use of a nurse answering service or even smart phones for wound evaluation has been shown to decrease presentation to the emergency department for nonacute issues. 14,15 Physicians on-call could have reassured Skin and soft tissue (10) 5 (50%) 0 (0%) 0 (0%) 10 (100%)…”
Section: Discussionmentioning
confidence: 99%
“…24 Chua et al showed that patients sending smartphone pictures of their operative sites after hypospadias repair to a urology clinic nurse had a significant decrease in rate of return to the emergency department (ED) for wound checks compared to those who did not send pictures (relative risk ÂŒ 0.14, p ÂŒ 0.01), but no difference in ED visits for other reasons. 26 Three other studies evaluating complication rates in patients undergoing multistage single-ventricle repair procedures using wireless monitoring systems found no significant differences in the number of unplanned ED visits between the mHealth and control groups. [27][28][29] Among those, Shirali et al had zero interstage deaths among the 30 patients using the CHAMP wireless monitoring system (a tablet app monitoring singleventricle patients at home during their interstage period) compared to nine deaths among 53 historical controls (17% mortality, p ÂŒ 0.023).…”
Section: Postoperative Follow-up Appointment Attendance Ratementioning
confidence: 93%
“…Free healthcare services providing health information have been touted as potentially useful solutions, preventing individuals entering the healthcare system at the wrong entry point (Hwang, Liao, Griffin, & Foley, 2012). This has included phone consultations (Hallfors, Saku, Makinen, & Madanat, 2018), and more recently the utilization of digital platforms (Bahadori, Teymourzadeh, & Mousavi, 2018) such as email and smartphone communications (Chua et al, 2017). These free services have the added benefit of being a potentially useful way to reach non-insured and/or low income groups which may benefit in particular with a trusted health information source (Hwang et al, 2012).…”
Section: Conceptual Backgroundmentioning
confidence: 99%